Biotechnological production of xylitol from oil palm empty fruit bunch, a lignocellulosic waste - Rahman, Siti Humairah Abd; Choudhury, Jyoti Prosad; Ahmad, Abdul Latif (Penerbit Universiti Sains Malaysia, 2004)
Palm oil mills in Malaysia generate approximately 15 million tons of oil palm empty fruit bunch (OPEFB) annually during processing of palm oil from fresh fruit bunch. This OPEFB fiber is a lignocellulosic waste which is renewable and contain high amount of xylan (approximately 24%), a polymer made of pentose sugar xylose. Hydrolyzing acid such as sulfuric acid, hydrochloric acid or hydrofluoric acid can be used as catalyst for reduction of xylan polymer to monomeric sugar xylose. Xylose is used as the starting material for xylitol production. During hydrolysis process other sugars such as arabinose, galactose, glucose and some unwanted components such as acetic acid and furfural are also released.